IDENTIFIKASI KOMPOSISI SAMPAH LAUT DI PESISIR ACEH BARAT - Ika Kusumawati; Mita Setyowati; Inseun Yuri Salena (JURNAL PERIKANAN TROPIS, 2018)
Marine Debris or Marine Liiter is a solid material that inadvertently or unintentionally left in the sea that has the impact of threatening the continuity and sustainability of marine life. Research on marine debris was conducted in West Aceh regency covering four coastal districts namely: Meurebo, Johan Pahlawan, Samatiga, and Arongan Lambalek. The purpose of this research is to identify the composition of marine debris in West Aceh district. So it can be as basic information to know the number and types of marine debris scattered in the coastal area of West Aceh regency, as well as for the related services in the management of marine debris. Data collection of marine debris is obtained by using line transects stretched along the coastline at the lowest tide. The results of research showed that Samatiga District is the most abundant area of marine debris with a total of 2300, then District Johan Pahlawan 1848, District Meureubo 281, and 145 District Arongan Lambalek. The most dominant composition of marine debris is found from all research locations divided (26.10%) Plastic Glass, (17.36%) Straw, and (14.95%) Food wrappers